Effect of gibberellic acid on the queen cell production and queen performance in colonies of Apis mellifera L. (Hymenoptera: Apidae) - Szawarski, Nicolás (2019)
For honey bees (Apis mellifera L.), the reward for pollination service is obtaining food: nectar, a sugar solution; or pollen, which contains a high percentage of proteins and lipids. There are also other floral rewards ecologically relevant for pollinators, like resins, and/or minor components, such as phytohormones and polyphenols. When rearing A. mellifera queens, several factors affect grafting success: age of the grafted larvae, design and position of the artificial queen cells, priming queen cells with royal jelly before grafting, or nutrition of the queen rearing colony. This study aimed to evaluate the effect of two phytohormones: gibberellic acid (GA) and indole acetic acid (IAA) on queen cell production, the development of hypopharyngeal glands of nurse bees, and the performance of queen bees in colonies of A. mellifera. The results indicate that GA positively influences queens production efficiency in vertical orphaned colonies and their reproductive performances in honey bee colonies. These results support the potential of plant metabolites as dietary supplements to improve queen bee production methods and their performance in colonies as well